PESTICIDE EXPOSURE OF BREAD SELLERS AND MICROBIAL SAFETY OF BREAD SOLD IN BAMENDA, CAMEROON - Jean SONCHIEU (Stefan cel Mare University of Suceava, 2018)
Safety of bread sold in Bamenda municipality has been always problematic because of the poor hygienic practices of sellers. This study aimed at assessing the microbial load of bread sold in Bamenda municipality and pesticides exposure of sellers. Ninety samples of bread were randomly collected from standard bakeries, local bakeries and roadside bread vendors; they were analyzed for total viable count, coliforms and yeast and molds (fungi) using the routine analytical method described by the American Public Health Association. The exposure of some bread vendors to pesticide shops was evaluated using questionnaires. As results, the total viable count ranged from 3.09 x 103 to 2.57 x 105cfu/g, coliform count ranged from 2.27 x 101 to 1.18 x 103cfu/g, while yeast and molds count ranged from 1.32 x 103 to 2.67 x 106cfu/g. Bread from roadside vendors was the most contaminated with molds, while the standard bread was the most contaminated with bacteria and coliforms. The local bread was the least contaminated. Sixteen bread sellers counted around pesticides shops presented ailments (Headache, eye irritation, etc.). Bread sold in Bamenda is contaminated by microbes and some vendors are exposed to pesticides.